Saint, hagiographer and translator St Jerome in the triumphal heavenly procession/translation in Štrigova (Croatia) - Cvetnić, Sanja 1961- (2021)
Fresco decoration in the sanctuary of the Church of St Jerome in Štrigova in north-western Croatia was completed in 1744 by Ioannes Baptista Ranger, the most prominent painter of the first half of the 18th century on the territory of the Zagreb Diocese. The three-foil ground plan of the sanctuary retains memory of an older-smaller church, erected before 1447, on the place that holds an enduring memory of St Jerome’s native soil, and from 1644 the church was in pastoral care of the Pauline order (Order of St Paul the First Hermit). The book Natale solum sancti Hieronymi (Native soil of St Jerome, 1752) by Joseph Bedeković was a part of a collective effort - mainly by Pauline authors, but not exclusively - to confirm Štrigova as St Jerome’s homeland, in particular in the eyes of the Bollandists, preparing at the time the volume containing the saint’s Vita. St Jerome was the hagiographer of the spiritual founder of the Pauline Order, St Paul the First Hermit. The most elaborate part of the fresco decoration is a procession in a tambour of a shallow dome that is interpreted as a Triumphal Heavenly Translation of St Jerome’s relics. They came from Bethlehem, where he was buried, to Santa Maria Maggiore in Rome, where the relics of St Jerome have reposed since the 13th century. First they were found near the older Chapel of the Manger (Cappella del Presepe), where the relics of the Sacra Culla or the Holy Crib were venerated as "Bethlehem in Rome". On that site the Sistine Chapel was later erected, and on the other side the Pauline Chapel with the icon Salus Populi Romani (copied in Štrigova). Both chapels are visible on the rear facade of the basilica, depicted as the destination of the miraculous procession.
Keywords: Ranger, Ivan Krstitelj -- 1700-1753; Hieronymus, Sophronius Eusebius -- 345-420; Heiligenbild; Freskomalerei; Hagiografie; Kirchenbau; Štrigova